Agro-biodiversity in Subsistence Farming Systems of South Somalia –Collection and Agronomic Assessment of Somali Sorghum (Sorghum bicolor (L.) Moench) Germplasm - Manzelli, M.; Benedettelli, S.; Vecchio, V. (Tropicultura, 2006)
After the collapse of Siyad Barre' regime, Somalia lost any form of agricultural research with negative consequences on food availability and seed sector stability. A fi rst step to restore food security can be represented by enhancing local genetic resources. Sorghum (Sorghum bicolor (L.) Moench) is a very important crop in rainfed areas of Somalia serving as primary source of food and forage. Eight morphological and productive characteristics were chosen to assess the phenotypic variability of 7 accessions from South Somalia. Univariate (ANOVA) and multivariate (discriminant and cluster analysis) methods were used to assess the productive variation within the accession and to group the 7 accessions into clusters based on quantitative characters. The results showed that there is a wide morpho-agronomical diversity among accessions, especially regarding specifi c features suitable for different purpose, such as grain and/or forage production. Moreover the landraces were able to grow and produce under harsh environmental conditions. The gathered information can be used to promote the conservation and future improvement of local sorghum landraces, thus aiding in the stabilisation of a secure and sustainable food resource for farmers of southern Somalia.